(untitled) (Northern International Medical College Journal, 2023)
Background : Children with Nephrotic Syndrome (NS) are exposed to multiple infections resulting in significant morbidity and mortality. Besides being a common cause of mortality, infections may also be responsible for a poor response to steroid therapy or induce relapse in a child with Nephrotic Syndrome. Aims: To assess the clinical spectrum of major infection in hospitalized children with Nephrotic Syndrome. Materials and Methods: This hospital based cross-sectional study was done in the Department of Paediatrics, Sylhet M A G Osmani Medical College Hospital, Sylhet, Bangladesh. In this study, sample size was 44 diagnosed cases of Nephrotic Syndrome with infection. After taking consent, detailed history and thorough physical examination were done in each patient. All data were collected in a preformed questioner and finally collected data were expressed in tabulated form. Results: In our study total 44 children with Nephrotic Syndrome were enrolled with the mean age of 5.98 ± 2.93 years and most of the childhood Nephrotic Syndrome was aged between 2 to 8 years (75.0%); 23 (52.3%) patients were male, and 21 (47.7%) patients were female with a ratio of male to female of 1.1:1. The common clinical symptoms of major infection were fever (79.5%) and cough (70.5%). Other clinical presentations were throat pain (18.2%), abdominal pain (15.9%), runny nose (11.4%), burning micturition (9.1%), respiratory distress (6.8%), vomiting (4.5%) and leg pain (4.5%). Relapse of Nephrotic Syndrome was found in 33 (75.0%) cases. The most common major infection was pneumonia (50.0%), followed by urinary tract infection (20.5%), Upper respiratory tract infection (15.9%), pneumonia with UTI (6.8%), cellulitis (4.5%) and pneumonia with UTI with spontaneous bacterial peritonitis (2.3%). The most common isolated organisms in urine were Escherichia coli (27.3%), followed by Klebsiella pneumoniae (2.3%). Conclusion: The common symptoms of major infection in Nephrotic Syndrome are fever and cough. The most common major infection was pneumonia and urinary tract infection. Northern International Medical College Journal Vol. 12 No.2 Jan 2021, Page 544-547